Between isolation and teaching: Obstacles to remote learning for students and teachers during social isolation - Macêdo, Brenno Luiz Silva; Dias, Márcia Adelino da Silva (Seven Editora, 2023)
The COVID-19 pandemic has created a challenging environment for society with respect to educating students and teachers, foundational agents, who have been enormously impacted by the isolation and adaptation to online courses. The new context led to the need to adapt not only for schools, but mainly for professionals, who, having to adapt their lives within social isolation to classes in the online role, where knowledge should be stimulated in the best possible way. The purpose of this work was to analyze the main difficulties of teachers and students for online classes, focusing primarily on adapting to emergency online education. This is a qualitative study, in which questionnaires were used to gather data to understand the difficulties experienced by the agents studied. It was possible to analyze and confirm several adversities that teachers were subjected to in the journey of online teaching, through the lack of specialization, many without an adequate work environment, challenging themselves to use new technologies, the difficulties of the students dealing with a weak internet connection, in addition to a large amount of activities, with little contact with the teacher, being the main difficulty actually understanding the importance of education at that moment, in addition to the eminent risk brought by the pandemic and the lack of financial stability. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-096